Promotional activities inside regulated markets. Impact of IQOS events on customer brand awareness and perception. - Martinelli, Veronica; Machek, Martin; Kolouchová, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Nowadays, the regulation of the tobacco market assumes a crucial role due to the scientifically proven harmful effect. Companies within this industry must respect some boundaries set by the legal framework on promotional activities. Despite this, the tobacco industry remains economically relevant and innovative, and therefore, it is essential to investigate how firms balance their profitability and social welfare. The main aim of this study is to investigate how the introduction of a heated tobacco product, IQOS, and its promotional activities modified customers' perception of a whole category. Two main sections were developed to reach this goal. A theoretical background to deepen the knowledge of the mentioned topics and a practical section based on qualitative interviews with IQOS users. The data collected have been analyzed and discussed with those of the theory to see if they support, complete, or question them. As a result, a more precise and complete picture emerged, highlighting how the IQOS brand successfully modified clients' points of view through its marketing activities. Within this context, legal entities must consider the influence of promotional activities on consumer perceptions. Emphasizing the need to develop regulations more congruent with current market developments.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses